Factors influencing students’ readiness for outsourcing their logistics - Rovšek, Vesna; Beškovnik, Bojan (Transport, 2017)
The purpose of the present paper is to contribute to better knowledge of consumer logistics and consumer preferences. This aspect of logistics is to our mind rather unexplored, but seems to be very important for the development of logistics companies. The paper is confined to the logistics executed by the younger population. The main goal of the research was to identify the factors influencing students’ readiness for outsourcing their logistics. Further, the survey aims at developing an instrument for measuring the scope and structure of the students’ logistics and the share of their mobility which they would be ready to have executed by the suppliers of logistic services. Two segments were statistically analysed: social-demographic data and the diary of travel behaviour. Among twenty-two independent variables, the results highlighted ‘length of journey’, ‘time necessary for the execution of logistics’ for the purpose of: ‘giving a ride to neighbours’, ‘shopping for consumer goods’, ‘change of residence’ and ‘entertainment’. Interestingly, it was ascertained that the more time the students travel by car, the more logistics they were prepared to outsource. Finally, the survey methodology applied might serve as the basis for further research into the market of logistic services as well as other aspects of consumers’ preferences referring to their logistics. Based on this, new means of public transportation might be designed and offered by various localities.First published online: 15 Jun 2015